The value of endocervical curettage for diagnosis of cervical precancers or worse at colposcopy of women with atypical glandular cells cytology - Chen, Yusha; Wen, Fanghong; Chen, Jiancui; Xue, Huifeng; Zheng, Xiangqin; Pan, Diling (Frontiers in Medicine, 2024)
Objective: This study evaluates the effectiveness of endocervical curettage (ECC) in identifying additional cervical cancer and its precursors in women with atypical glandular cells (AGC) cytology. Methods: We conducted a retrospective analysis of medical records for women referred to colposcopy with AGC cytology between January 2019 and December 2023. The study included 433 women with AGC cytology who underwent both biopsy and ECC. Clinical characteristics such as demographics, clinical history, cytology, HPV status, colposcopic findings, and pathology were analyzed. Chi-square and Fisher's exact tests were applied to compare the characteristics of ECC-diagnosed cervical precancers or worse (HSIL+) and normal/low-grade squamous intraepithelial lesions (LSIL).The overall detection rate of HSIL+ in this population was 19.4% (86/443), with ECC alone identifying HSIL+ in 1.3% (6/443) of cases. However, ECC showed greater utility in certain subgroups. The highest additional HSIL+ detection from ECC was observed in women with HPV 16/18 infection (7.2%) and those with AGC-FN cytology (4.4%). ECC's additional yield of HSIL+ was higher in those with normal or LSIL colposcopic impressions compared to those with HSIL+ impressions. Conversely, no additional HSIL+ cases were identified by ECC alone in women under 30 years old, those with negative high-risk HPV results, or those with type 1/2 transformation zones.For women with AGC cytology, ECC should be performed in patients with AGC-FN cytology, HPV 16/18 infections, type 3 transformation zones, and normal or low-grade colposcopic impressions. This approach enhances the identification of HSIL+ cases by reducing false negatives. However, for women younger than 30 years old and those with type 1/2 transformation zones, ECC offers limited benefit.